2017
DOI: 10.1002/pamm.201710366
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a running gear with IRWs on curved tracks for a robust control development

Abstract: As a major task of the DLR-internal project "Next Generation Train", robust state feedback control with gain scheduling was sucessfully applied to guide the experimental running gear with independently rotating wheels (IRWs) at a 1:5 scaled roller rig, see [1]. However, the adaptation of the control structure to the 1:1 multibody model requires to additionally consider the properties of curved tracks. For that reason, an analytical model of a running gear with IRWs is deduced using Euler-Lagrange-equations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
(2 reference statements)
0
8
0
Order By: Relevance
“…in the transition curve. The problem can be overcome with a feedforward approach dedicated to solve the delay problem in transition curve as proposed in [15,29] or by using signals coming from the preceding vehicles as done in tilting trains ( [21]). Nevertheless, in the circular part of the curve, a reduction of approximately 92% for the 175 m curve 75% for the 711 m curve in terms of Tγ function for the trailing wheelset is achieved while a reduction of 99% for the 175 m curve and 97% for the 711 m curve is observed for the leading wheelset.…”
Section: Results On Feedforward Approachesmentioning
confidence: 99%
“…in the transition curve. The problem can be overcome with a feedforward approach dedicated to solve the delay problem in transition curve as proposed in [15,29] or by using signals coming from the preceding vehicles as done in tilting trains ( [21]). Nevertheless, in the circular part of the curve, a reduction of approximately 92% for the 175 m curve 75% for the 711 m curve in terms of Tγ function for the trailing wheelset is achieved while a reduction of 99% for the 175 m curve and 97% for the 711 m curve is observed for the leading wheelset.…”
Section: Results On Feedforward Approachesmentioning
confidence: 99%
“…The design of the reward function is essential for guiding agents to optimize toward the control objective efficiently. For an IRW vehicle, the MARL-based controller aims to improve straight-line stability and curve-negotiation capabilities, which can be achieved by implementing control methodologies, including zero lateral clearance [23] and radial control [24]. Specifically, zero lateral clearance aims to maintain the geometric center alignment of the IRW with the track centerline, minimizing lateral displacement.…”
Section: Reward Shapingmentioning
confidence: 99%
“…The motors can be externally mounted and connected to the wheelset through a gearbox (Pérez et al [137], Liang et al [139,140], Ahn et al [141], Lu et al [142] and Farhat et al [98,143]) as shown in Fig. 30 or embedded inside the wheels (Mei et al [144], Ji et al [145] and in the 'Next Generation Train' project in [124], [146][147][148][149]). The absence of additional actuators leads to a reduction in the space required by the wheelset frame, and to the possibility to provide both traction and control within the same system reducing cost and improving reliability.…”
Section: (B) Driven Independently Rotating Wheel (Dirw)mentioning
confidence: 99%
“…Using the same control approach but focusing on the synchronous motor control, Ahn et al [141] successfully showed the effectiveness of this control scheme on a 1:5 scaled test rig. A feedforward action was introduced by Grether in [147] to compensate the gyroscopic moment introduced into the system in transition curves. This concept was then used by Heckmann et al [148] in combination with a feedback control on lateral displacement, yaw angle and yaw velocity of the wheelset.…”
Section: B3 Zero Lateral Clearancementioning
confidence: 99%